Digital media in promoting activism the case of Galang Philippines - Naquita, Rugene; Velasco, Stephanie Joy. (2016.)
This study entitled Digital Media in Promoting Activism: The Case of Galang Philippines is a descriptive research on how Galang Philippines uses their Facebook account in promoting feminist activism. It describes the step by step process of Galang Philippines in promoting its cause through social media and determines the value of Facebook as a tool for activism. The research, anchored on the Media Gatekeeping theory by Kurt Lewin and the 4 Models of Public Relations by James Grunig and Todd Hunt, uses the key-informant technique through purposive sampling. Researchers conclude that the organization follows a gatekeeping process consistent with its rules but passive in nature because they do not consider feedback from the audience. This makes the digital activism by Galang Philippines consistent with the Public Information Model. The researchers recommend that Galang Ph should develop a feedback mechanism on their Facebook page in order to be more interactive with their audience. They also recommend that future researchers study how other organizations use social media platforms to explore best practices in digital activism.
Thesis -- Bachelor of Arts in Communication and Media Studies. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Digital activism; Facebook; Galang; Public information model